2020
DOI: 10.34172/japid.2020.010
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of periodontitis and associated factors in previously treated periodontitis patients without maintenance follow-up

Abstract: Background. Preventive dentistry, including supportive periodontal therapy (SPT), is one of the most critical areas of attention. Despite SPT’s importance in the long-term success of periodontal treatment, the patients’ adherence to it is weak. The present study aimed to evaluate of periodontal disease’s recurrence rate and its related factors in periodontal patients without regular follow-up. Methods. A cross-sectional study was set in a specialized periodontics clinic in Tehran, Iran. Patients with periodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Compliance with scheduled maintenance intervals has been emphasized in previous studies (Agrawal et al, 2015;Atarbashi-Moghadam et al, 2020). However, no specific definition has been established for 'compliant' and 'noncompliant' in this review owing to the restriction in available information and reported data.…”
Section: Methodological Considerations and Study Limitationsmentioning
confidence: 96%
“…Compliance with scheduled maintenance intervals has been emphasized in previous studies (Agrawal et al, 2015;Atarbashi-Moghadam et al, 2020). However, no specific definition has been established for 'compliant' and 'noncompliant' in this review owing to the restriction in available information and reported data.…”
Section: Methodological Considerations and Study Limitationsmentioning
confidence: 96%
“…However, treatment of C. albicans and P. gingivalis is quite different, and co-treatment has not yet been investigated in molecular detail 21 . Treatment for P. gingivalis -based gingivitis is largely limited to lifestyle changes; thus, gingivitis relapses are common in susceptible patients leading to tooth loss and worse quality of life 24 . Moreover, drug-resistant fungi are a growing public health threat with a mortality rate as high as 30% in the Candida family ( C. auris ); thus, improved therapies are clearly needed 3 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive periodontal therapy, which combines non-surgical and surgical periodontal therapy, has been shown to be effective in achieving adequate attachment gain [2]. Periodontal maintenance, also known as supportive periodontal therapy (SPT), is a phase of periodontal therapy in which the periodontal condition is monitored and etiological factors are reduced or eliminated following periodontal treatment [3,4,5]. Following active periodontal therapy, maintenance consists of three components: patient personal care, preventive procedures performed by dental health care professionals, and supportive periodontal therapy interventions addressing disease recurrence due to re-emergence of subgingival biofilm and pocket formation [6].…”
Section: Introductionmentioning
confidence: 99%